PSYCHOLOGICAL EFFECTS OF COLOR (A STUDY IN THE CONTEXT OF ADOLESCENT GIRLS): रंगो का मनोवैज्ञानिक प्रभाव (किशोरियों के संदर्भ में एक अध्ययन) - Sengupta, Geetali (International Journal of Research -GRANTHAALAYAH, 2014)
Humans have a fondness for colors, not from today but for centuries. Color is the most valuable gift of nature and God. Life cannot be imagined without color. The diverse colors of countless objects composed by nature have been sources of inspiration. On seeing them, man has engraved him in paintings, sculptures, dramas and literature. We get continuous energy and enlightenment power through colors, of course, colorless life is dull, indifferent and monotonous. Man is a lover of beauty by nature. Therefore, he has a close relationship with colors. He has learned to create different colors first from nature and then gradually from scientific experiences and has started his life with colors. रंगों के प्रति मानव का अनुराग आज से नहीं बल्कि सदियों से रहा है। रंग प्रकृति एवं ईष्वर की सबसे बहुमूल्य देन है। रंग के बिना जीवन की कल्पना भी नहीं की जा सकती है। प्रकृति द्वारा रचित अनगिनत वस्तुओं के विविध रंग प्रेरणा के स्त्रोत रहे हैं। इन्हें देखकर मनुष्य ने उसे चित्रकलाओं, मूर्तिकलाओं, नाट्य एवं साहित्य में उकेरा है। रंगों से हमें निरन्तर ऊर्जा एवं चैतन्य शक्ति प्राप्त होती है, निष्चित ही रंगविहीन जीवन नीरस, उदासीन एवं एकसार होता है। मनुष्य स्वभाव से सुन्दरता प्रेमी है। अतः रंगों से उसका घनिष्ठ सम्बन्ध रहा है। पहले प्रकृति से फिर धीरे-धीरे वैज्ञानिक अनुभवों से उसने विभिन्न रंगों का सृजन करना सीख लिया है और अपने जीवन को रंगों से सरोवार कर लिया।